FRI0446 Ultrasonography of Large Epiaortic Arteries in Patients with GIANT Cell Arteritis. (10th June 2014) - Hočevar, A.; Rotar, Ž.; Praprotnik, S.; Tomšič, M.
Abstract : Background: Giant cell arteritis (GCA) is the most common systemic vasculitis in patients over 50 years of age. In Slovenia it has an annual incidence rate of 10.5 per 10 5 adults aged 50 or above. It affects large and medium-sized arteries, most commonly the extracranial branches of the carotid arteries, the ascending aorta, subclavian, and axillary arteries. Recently, the Colour-Doppler sonography (CDS) has gained momentum as a potential non-invasive tool for evaluation of large arteries in large vessel vasculitides. Objectives: To evaluate the involvement of large epiaortic arteries in patients with GCA using CDS. Methods: CDS of large epiaortic arteries was prospectively performed by a single assessor (AH) on a Philips IU22 using a 5–17.5 MHz linear probe in patients with newly diagnosed GCA prior to or up to 2 days after starting glucocorticoids. Carotid, vertebral, thyroid, subclavian, and axillary arteries were assessed in longitudinal and transversal planes. The "halo sign" (i.e. a hypoechoic circumferential wall thickening), vascular stenosis (i.e. >50% reduction of the original lumen) or occlusions were considered a positive finding. Results: From September 2011 to December 2013 CDS of large epiaortic arteries was performed in 48 GCA patients fulfilling the American College of Rheumatology criteria for the classification of GCA. In 13 (27.1%) patients involvement of epiaortic large arteries was found. A single artery was affected in 6 patients, and 7 patients had more than one epiaortic artery affected. In nine patients bilateral involvement was observed (Table 1 ). When patients with large artery involvement were compared to the patients with no large artery involvement the former were more commonly female (F:M ratio 5.5 vs. 1.9; p=0.2) and had had a longer disease duration (11.6 weeks vs. 6.4 weeks, p=0.1), yet differences were not statistically significant. Neither were there any statistically significant differences in the clinical presentation (i.e. presence of general symptoms, polymyalgia rheumatica, new onset of headache, jaw claudication, visual disturbances, changes of temporal arteries on physical examination) nor the levels of systemic markers of inflammation between the two groups. 77% and 90% GCA patients with epiaortic vessel disease had positive temporal artery CDS and biopsy respectively (vs. 88% and 83% GCA patients without large vessel disease). Two out of 13 patients with large vessel involvement by CDS had had a negative CDS of temporal arteries as well as a negative temporal artery biopsy. Conclusions: Large artery involvement was demonstrated in more than 1/4 of our GCA cases. CDS of epiaortic large arteries in addition to CDS of temporal arteries increases the diagnostic yield in GCA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1964